Performance of an occupational therapist in a neonatal intensive care unit - Rubio Grillo, María Helena (Colombia medica (Cali, Colombia), 2019)
Abstract Background: The following article constitutes an effort to make explicit an experience in neonatology within the framework of the exercise of occupational therapy, a discipline belonging to the health sciences. The occupational therapist (OT) in the Neonatal Intensive Care Unit in which he participates in an interdisciplinary health group. Exalts the interaction of person-environment-occupationperformance. Encourage self-regulation of the baby. Encourages family participation in co-participation in routine activities. Objective: To determine the realities and knowledge about the practice of OT in the Neonatal Intensive Care Unit (NICU) by the occupational therapist in the interaction between the baby, the occupation, the caregivers and the environment of the NICU. Methods: A systematic exploratory review of the performance of the OT in the NICU was made. Results: The results transcended the thematic variables, the theories, the methods, the approaches, the characteristics of the baby, the occupations, and the contexts of the management of the premature baby. Conclusion: The education in concepts concerning the occupation of the baby, the interaction with her/his environment and her/ his caregivers, the procedures, the guide for the stimulation as the modification of the physical, temporal and social environment facilitate the self-regulation of the baby and we will all be working in pro of your recovery.